2020
DOI: 10.1186/s12864-020-07024-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptome and metabolome analyses of two types of rice during the seed germination and young seedling growth stages

Abstract: Background: Seed germination and young seedling growth are important agricultural traits for developing populations of both irrigated and directly seeded rice. Previous studies have focused on the identification of QTLs. However, there are few studies on the metabolome or transcriptome of germination and young seedling growth in rice. Results: Here, an indica rice and a japonica rice were used as materials, and the transcripts and metabolites were detected during the germination and young seedling growth perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Dataset GSE115371 provided gene expression data at 0 h, 1 h, 3 h, 12 h, 1 d, 2 d, 3 d and 4 d timepoints after imbibition, for an Australian variety (Amaroo); only timepoints from aerobically grown samples were used (Narsai et al 2017). DEGs were identi ed by comparing expression at different timepoints to expression at 0 h. Dataset SRP277875 provided expression data for a japonica variety (02428) and an indica variety (YZX) at 2, 3, and 4 days after imbibition compared with a 0 h timepoint (Yang et al 2020). The data of the japonica variety was used for expression comparison of candidate genes (Fig.…”
Section: Gwas and Candidate Gene Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dataset GSE115371 provided gene expression data at 0 h, 1 h, 3 h, 12 h, 1 d, 2 d, 3 d and 4 d timepoints after imbibition, for an Australian variety (Amaroo); only timepoints from aerobically grown samples were used (Narsai et al 2017). DEGs were identi ed by comparing expression at different timepoints to expression at 0 h. Dataset SRP277875 provided expression data for a japonica variety (02428) and an indica variety (YZX) at 2, 3, and 4 days after imbibition compared with a 0 h timepoint (Yang et al 2020). The data of the japonica variety was used for expression comparison of candidate genes (Fig.…”
Section: Gwas and Candidate Gene Selectionmentioning
confidence: 99%
“…To further nd eSNPs associated with seed germination, we compared expression in the japonica and indica varieties in dataset SRP277875 (Yang et al 2020). More than twice as many genes were upregulated in the japonica than in the indica variety (Online Resource 5), suggesting that the germination difference between these two rice subpopulations can be caused by the differential expression of genes.…”
Section: Esnps Associated With Seed Germinationmentioning
confidence: 99%
“…However, Wang et al ( 2020 ) only identified 57 metabolites in mung bean by untargeted metabolome analysis performing gas chromatography-mass spectrometry (GC-MS), and most of the metabolites were sugar metabolism compounds, amino acid metabolism compounds, tricarboxylic acid (TCA), and other organic acid metabolism compounds. Seven hundred thirty metabolites were detected in the germination and post-germination growth stages of the two varieties of rice by widely targeted metabolome, including 32 substances and their derivatives, among which flavone (74, 10.1%), organic acids (67, 9.2%), amino acid derivatives (60, 8.2%), nucleotide and its derivates (57, 7.8%), and flavone C-glycosides (44, 6.0%) accounted for the largest proportion (Yang et al, 2020 ). This indicated that the widely targeted metabolome method could identify more metabolites than the untargeted metabolome method, and the metabolites of rice were far more than that of M. pasquieri , which may be related to the different species and germination stages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 78.7–83.9% of the reads were mapped on the mung bean reference genome (Wang et al, 2020 ). The average rates of mapped transcripts for the indica rice and japonica rice in the Nipponbare reference genome were 80.94 and 80.27%, respectively (Yang et al, 2020 ). This is because M. pasquieri lacks genomic information and only full-length transcriptome sequences are used as reference sequences, while the third-generation sequencing uses mixed samples, which may filter some low-quality reads during assembly, and the transcript length is longer, leading to a relatively lower mapped rate with the single RNA-Seq samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation